2010
DOI: 10.1080/00986283.2010.488554
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Science is Not Enough: The Influence of Classroom Experiences on Belief in Paranormal Phenomena

Abstract: Beliefs in scientifically unsubstantiated ideas were investigated with a study that contrasted college students' attitudes toward paranormal phenomena before and after exposure to skeptical arguments concerning these events. Specifically, students enrolled in 2 sections of a psychological statistics course were exposed to illustrations of statistical concepts that were either paranormal-themed or not, with a 3rd group of participants completing a class that focused on the critical analysis of believer-and skep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…This was not the case across all of the studies reviewed. A trend that is emphasized when one contrasts intervention groups comprised of lower level students with comparison groups comprised predominantly of upper level students (e.g., Burke et al, 2014, Manza et al, 2010, Morier & Keeports, 1994. This finding is especially disconcerting when it is considered that both the American and Canadian Psychological Associations assert that critical thinking skills, including scientific reasoning and the ability to evaluate evidence, are a primary goal of psychology education (American Psychological Association, n.d.; Norcross et al, 2016;Service & O'Neill, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case across all of the studies reviewed. A trend that is emphasized when one contrasts intervention groups comprised of lower level students with comparison groups comprised predominantly of upper level students (e.g., Burke et al, 2014, Manza et al, 2010, Morier & Keeports, 1994. This finding is especially disconcerting when it is considered that both the American and Canadian Psychological Associations assert that critical thinking skills, including scientific reasoning and the ability to evaluate evidence, are a primary goal of psychology education (American Psychological Association, n.d.; Norcross et al, 2016;Service & O'Neill, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Students taking this course showed a decrease in their paranormal beliefs after completing the course and an improvement in their critical thinking skills. However, similar to Manza et al (2010), students enrolled in a research methods course that did not incorporate the topics of identifying pseudoscience did not show any change in their paranormal beliefs, although they did improve their critical thinking abilities. McLean and Miller suggest that direct instruction in parapsychology and pseudoscience might be necessary to influence students' paranormal beliefs.…”
mentioning
confidence: 88%
“…However, in both Manza et al and McLean and Miller, the ''non-paranormal'' course used for comparison did not address the elements of pseudoscience. The comparison courses focused on lower-level statistics (Manza et al, 2010) or on statistical concepts and research methods (McLean & Miller, 2010). It may be too big of a leap for students to move from thinking about statistics to evaluating the paranormal, even if critical thinking abilities are relevant to each area.…”
mentioning
confidence: 99%
“…Specific subjects the belief in which was decreased were the following: psychic ability, witchcraft, spiritualism, and precognition. Furthermore, students exposed to a class that directly confronted paranormal phenomena in the context of known science reduced their belief in the paranormal over the course of the semester (Manza et al 2010).…”
Section: The Effect Of a Critical Thinking Course On Beliefmentioning
confidence: 99%
“…For example, it was found that the paranormal beliefs of participants (> 55 years old) were reduced following a 1-week course in skeptical inquiry (Banziger 1983). Similarly, students in a course dedicated to skeptical investigation of parapsychology had a 32-45% decrease in paranormal beliefs (McLean and Miller 2010;Manza et al 2010). Students exposed to methods of critical thinking and evaluation of experimental design lowered their paranormal beliefs by 10% (Stark 2012), and the more scientific knowledge students had the more they rejected paranormal subjects (Bensley et al 2014).…”
Section: Introductionmentioning
confidence: 99%